Moving from North to North: how are the students’ university flows? - Rizzi, Laura; Grassetti, Luca; Attanasio, Massimo (Genus, 2021)
Student mobility has been much commented upon and much studied. Student mobility has social, economic, and political consequences. This form of mobility is relevant, in Italy, in terms of south-north flows, while the mobility of northern students toward the South and Centre of Italy is negligible. To the best of our knowledge, a proper focus on the dynamics among northern regions has not yet been carried out. This study focuses on the interregional mobility of northern first-year students. To this end, we use a longitudinal dataset with students’ individual histories from 2008 to 2017, obtained from the cohort-based datasets collected using the Italian Ministry of University’s administrative databases. Descriptive and model-based analyses are employed for assessing the association between the propensity to move and individual characteristics, as well as some territorial variables. A longitudinal study is also considered. Here, we see an increase in the population entering the university system and mobility flows across northern regions. The results show that students’ educational experiences influence the propensity to move. However, the most relevant driver of the phenomenon is the attractiveness of areas with a higher supply of university courses and a better economic context.